Utility of urinary liver-type fatty acid-binding protein as a predictor of renal dysfunction in Japanese patients with HIV receiving tenofovir disoproxil fumarate with low urinary β2 microglobulin levels: a retrospective observational study - Shinichi Hikasa; Shota Shimabukuro; Kyoko Hideta; Satoshi Higasa; Akihiro Sawada; Tazuko Tokugawa; Kuniyoshi Tanaka; Mina Yanai; Takeshi Kimura (BMC, 2019)
Abstract Background Tenofovir disoproxil fumarate (TDF) is known to reduce estimated glomerular filtration rate (eGFR). It is clinically important to identify patients at high risk for renal dysfunction as early as possible. Among the tubular markers, urinary β2 microglobulin (Uβ2MG) is a well-known biomarker of TDF-related tubulopathy. However, renal dysfunction has often been occurred in patients receiving TDF with low Uβ2MG levels. Recently, urinary liver-type fatty acid-binding protein (UL-FABP) was suggested to be predictor of the progression of renal dysfunction. Thus, we focused on UL-FABP in patients receiving TDF with low Uβ2MG levels. Methods A retrospective, observational, single-center study, between January 2013 and December 2016, was conducted. Two renal end points (> 25% decrement in eGFR and > 20 mL/min/1.73 m2 decrement relative to the baseline) were assessed. To estimate the effect of UL-FABP on time to the first event, log-rank test was performed. Results A total of 24 Japanese outpatients with human immunodeficiency virus receiving TDF were enrolled. The outcome each occurred in two patients during the follow-up period. UL-FABP levels ≥4.0 μg/g creatinine was significantly associated with > 25% decrement and > 20 mL/min/1.73 m2 decrement (p = 0.006 and 0.001, respectively). Conclusion Based on our preliminary analysis, UL-FABP levels ≥4.0 μg/g creatinine predict renal dysfunction in patients receiving TDF with low Uβ2MG levels.